Preferensi pangan fungsional dan implikasinya terhadap kesehatan masyarakat: Tinjauan sistematis - Risa Nur Amalia; Anita Rahmiwati; Nur Alam Fajar; Novrika Sari (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Currently, there is an increase in public awareness and interest in consuming functional foods as part of a healthy lifestyle. People tend to be more interested in food products that not only meet basic nutritional needs but also provide additional health benefits, such as disease prevention. Understanding the complex factors that influence functional food preferences in society is very necessary to develop efforts to improve public health.Objective: To determine the determinants of functional food consumption preferences in society and their implications for efforts to improve public health.Method:  This research was prepared using a Systematic Review design with the Preferred Reporting Items for Systematic Reviews (PRISMA) approach. The data used as a reference for this research comes from international scientific publications in the PubMed, ScienceDirect, Emerald Insight and Taylor & Francis databases. The data search process was carried out using relevant keywords such as Functional Food, Consumption, Preferences, Public Health, Factor, and Determinant. This combination of keywords is applied using boolean operators. The articles collected are articles published in the 2019-2023 period.Results: A systematic review of a synthesis of 11 selected articles shows that functional food consumption preferences in society are influenced by various complex factors, including demographic aspects, food choice motives, living situations, economic factors, health perceptions, sensory, psychological and lifestyle characteristics. These preferences have significant implications for efforts to improve public health.Conclusion: Determinants of functional food consumption preferences include demographic aspects, food choice motives, living situations, economic factors, health perceptions, sensory, psychological characteristics and lifestyle.KeywordsFunctional food consumption, functional food preferences, public health